Akuntansi Berkelanjutan: Implementasi Standar Pelaporan Keberlanjutan dalam Praktik Bisnis CV. Utami - Nenden Restu Hidayah; Karona Cahya Susena; Heskyel Pranata Tarigan (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
This article explores the implementation of sustainability reporting standards in the business practices of CV. Utami, a small and medium-sized company in the local service sector. Involving a case study, this research explores CV Utami's journey in integrating sustainable accounting practices in their operations. The results show the company's increasing awareness of sustainability issues and their impact on society and the environment. Through interviews, document analysis, and field observations, this article identifies the concrete steps taken by CV Utami in implementing sustainable accounting practices. The company successfully applies sustainability reporting standards such as the Global Reporting Initiative (GRI) as the main framework in measuring and reporting their sustainability performance. The benefits of sustainable accounting practices, including improved corporate reputation, attractiveness to social and environmental investors, and enhanced ability to manage sustainability risks, are also discussed. In addition, the challenges faced by CV Utami in terms of allocation of limited financial and human resources. The importance of engagement with external parties such as local government, non-governmental organisations, and local communities in the context of sustainable accounting is also emphasised. This article shows how external partnerships can broaden a company's view of social and environmental responsibility and provide tangible benefits in facing sustainability challenges. Through the case study of CV Utami, this article provides insights into how small and medium-sized enterprises can play a significant role in driving positive change towards more sustainable businesses. Awareness, commitment and co-operation with external parties form the basis for successful implementation of sustainable accounting practices.